Reconstructing Neanderthal diet: The case for carbohydrates. Issue 162 (January 2022) - Hardy, Karen; Bocherens, Hervé; Miller, Jennie Brand; Copeland, Les
Abstract: Evidence for plants rarely survives on Paleolithic sites, while animal bones and biomolecular analyses suggest animal produce was important to hominin populations, leading to the perspective that Neanderthals had a very-high-protein diet. But although individual and short-term survival is possible on a relatively low-carbohydrate diet, populations are unlikely to have thrived and reproduced without plants and the carbohydrates they provide. Today, nutritional guidelines recommend that around half the diet should be carbohydrate, while low intake is considered to compromise physical performance and successful reproduction. This is likely to have been the same for Paleolithic populations, highlighting an anomaly in that the basic physiological recommendations do not match the extensive archaeological evidence. Neanderthals had large, energy-expensive brains and led physically active lifestyles, suggesting that for optimal health they would have required high amounts of carbohydrates. To address this anomaly, we begin by outlining the essential role of carbohydrates in the human reproduction cycle and the brain and the effects on physical performance. We then evaluate the evidence for resource availability and the archaeological evidence for Neanderthal diet and investigate three ways that the anomaly between the archaeological evidence and the hypothetical dietary requirements might be explained. First, Neanderthals may have had an as yet unidentified genetic adaptation to an alternative physiological method to spare blood glucose and glycogen reserves for essential purposes. Second, they may have existed on a less-than-optimum diet and survived rather than thrived. Third, the methods used in dietary reconstruction could mask a complex combination of dietary plant and animal proportions. We end by proposing that analyses of Paleolithic diet and subsistence strategies need to be grounded in the minimum recommendations throughout the life course and that this provides a context for interpretation of the archaeological evidence from the behavioral and environmental perspectives.